Prenatal diagnosis of right-sided congenital diaphragmatic hernia - Sokołowski, Łukasz; Pałgan, Magdalena; Strzelecka, Iwona; Sylwestrzak, Oskar; Krekora, Michał; Tadros-Zins, Monika; Grzelak, Piotr (Prenatal Cardiology, 2023)
This case report details the prenatal diagnosis and management of a right-sided congenital diaphragmatic hernia (CDH) in a 37-year-old pregnant woman. In the 22nd week of the pregnancy, a screening ultrasound revealed an abnormal mass in the right fetal chest, suspected to be a diaphragmatic hernia. A series of fetal ultrasound and echocardiographic examinations were conducted, revealing a mass of intestines in the right chest displacing the heart (with normal heart anatomy). Fetal magnetic resonance imaging at 27 weeks confirmed the diaphragmatic hernia. Subsequent monitoring revealed unfavourable prognostic indicators, including a decreased lung-to-head ratio (LHR) index. Premature rupture of membranes occurred in the 28th week. An urgent caesarean section was performed at 31 weeks due to the onset of labour and signs of fetal distress, and a female newborn with a birth weight of 1800 g was delivered. Right-sided diaphragmatic hernia was confirmed postnatally. Surgical intervention was undertaken to relocate the intestines and close the diaphragmatic defect. Despite initial efforts, the newborn’s respiratory and circulatory function deteriorated, leading to the unfortunate demise on the sixth day of life.